1983
DOI: 10.1002/prep.830080302
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of high energy compounds. I. Trans‐1,4,5,8‐tetranitro‐1,4,5,8‐tetraazadecalin (TNAD)

Abstract: The synthesis of a new high‐energy compound trans‐1,4,5,8‐tetranitro‐1,4,5,8‐tetraazadecalin is described. The compound has a density of 1.80 g/cm3 and a heat of formation of 17.5 kcal/mol. The detonation pressure is calculated to be 310 kbar and the detonation velocity is calculated to be 8.36 mm/μs by the Kamlet Short Method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…For comparisons, the experimental detonation performance of HMX, bicycle-HMX, and TNAD is also tabulated in Table together with another known explosive RDX. The calculated detonation velocities and pressures agree well with the available experimental data, with the relative errors +1.43% and −1.10% for HMX (A1), +0.65% and −8.57% for bicycle-HMX (B11), +2.87% and +5.90% for TNAD (C11), and +1.37% and +2.35% for RDX, respectively. This reflects that our predictions for the title compounds are reliable and further confirms the reliability of the calculation method used for these molecular systems.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…For comparisons, the experimental detonation performance of HMX, bicycle-HMX, and TNAD is also tabulated in Table together with another known explosive RDX. The calculated detonation velocities and pressures agree well with the available experimental data, with the relative errors +1.43% and −1.10% for HMX (A1), +0.65% and −8.57% for bicycle-HMX (B11), +2.87% and +5.90% for TNAD (C11), and +1.37% and +2.35% for RDX, respectively. This reflects that our predictions for the title compounds are reliable and further confirms the reliability of the calculation method used for these molecular systems.…”
Section: Resultssupporting
confidence: 81%
“… a Data in parentheses are the experimental values taken from refs . b For the explosive C a H b O c N d : OB (%) = 1600 × ( c – 2 a – b /2)/ M w , where M w is the molecular weight. …”
Section: Resultsmentioning
confidence: 99%
“…[38][39][40][41] Many research groups [42][43][44][45] over the past decades reported energetic materials rich in nitro groups. Selected examples of some familiar oxygen-rich and nitrogen rich explosives such as 1,3,5-trinitrotriazacyclohexane (RDX), [46] 1,3,5,7-tetranitrotetraazacyclooctane (HMX), [47] hexanitrobenzene (HNB), [48] trinitrotoluene (TNT), [49] 4,10-dinitro-4,10-diaza-2,6,8,12-tetraoxaisowurtzitane (TEX), [18,50] trans-1,4,5,8-tetranitro-1,4,5,8-tetraazadecalin (TNAD), [51] penta-erythritol tetranitrate (PETN), [52] hexanitrostilbene (HNS), [53] tetraazidomethane (TAM), [54] 2,2,4,4,6,6-hexanitroadamantane (HNA), [55] 4,4'-Azobis [1,2,4-triazole] (ABTr), [56] along with promising candidates for insensitive munitions (IM) such as 1,1-diamino-2,2-dinitroethylene (FOX-7), [57] 5-nitro-1,2,4triazole-3-one (NTO), [58] and triaminotrinitro benzene (TATB), [59] have been reported in literature.…”
Section: Introductionmentioning
confidence: 99%
“…27 The strength of bonding is fundamental to understanding the chemical process, which could be evaluated from the BDE. 21,22 Originally, it is defined as the enthalpy change at 298 K and 1.01×10 5 Pa for the chemical bond dissociation in a molecule A-B as follows:…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] Among them, the explosive trans-1,4,5,8-tetranitro-1,4,5,8-tetraazadecalin (TNAD, Figure 1) was characterized as a promising high energy density material (HEDM) with superior shock sensitivity and thermal stability. 5 It was reported to melt in 232-234 ℃ and decompose only above 220 ℃ according to the thermogravimetry (TG) and differential thermal analysis (DTA). 6 The measured impact sensitivity h 50% (in terms of the height from which a falling 2.5 kg weight will cause detonation 50% of the time) is 35 cm, comparable to the values of 25-28 cm for RDX (1,3,5-trinitro-1,3,5-triazocyclohexane) and 18-26 cm for HMX (1,3,5,7-tetranitro-1,3,5,7-tetraazacyclooctane) that are among the most effective and widely-used explosives and monopropellants.…”
Section: Introductionmentioning
confidence: 99%